The Dualism Phenomenon of Covid-19 Prevention Policy at Entikong Border, West Kalimantan Province: A Government Communication Study - Wuysang, Julia Magdalena; Iriansyah, Adibrata; Patriani, Ira; Rahmawati,; Pijoh, Feibe Engeline (Technium Social Sciences Journal, 2024)
Entikong District, Sanggau Regency, West Kalimantan Province, is one of the border areas of Indonesia and Malaysia. Among several Cross-Border Posts (PLBN) in the Indonesian territory, one of them was established in Entikong Sub-district, Entikong PLBN. The Entikong area was equally impacted by the Covid-19 pandemic. Aiming to prevent the spread of the COVID-19 virus in Entikong, the government issued two policies. The first policy was to close the border. Despite being closed, the border remained accessible for Indonesian citizens intending to return to Indonesia and foreign nationals with visas according to certain conditions. The second policy was the Enforcement of Micro-based Community Activity Restrictions (PPKM). Both emerged as two conflicting policies where the border was closed but accessible for Indonesian citizens, such as returning Indonesian migrant workers and foreigners with certain visas. However, on the other hand, PPKM restricted the mobility of the Entikong community. It is certain that these two policies greatly impacted the community residing in the Entikong border area due to the absence of socialization and intense communication for the community in West Kalimantan, which possesses a number of border entry points.